NOTES ON THE FORMATION OF HILYA DESIGN: CALLIGRAPHY-ILLUMINATION INTERACTION AND NUMERAL SYMBOLISM - KÜPELİ, GÜLNİHAL (My University, 2019)
In Ottoman tradition of thought the Prophet Muhammad represents the complete human being (al-insan al-kamil), who has reached the highest psychological, physical and spiritual stage of being. In this case the main purpose of the hilya as a work of calligraphy and illumination is to aesthetically evoke the physical appearance and moral character of the Prophet Muhammad. Moreover, the complex symbolism of the hilya as an expression of prophetic glory also reflects the cosmological thought of the Ottoman community. The subject of this article is to examine the classical hilya design attributed to the famous Ottoman calligrapher Hâfiz Osman in the context of calligraphy-illumination interaction and number symbolism. Examining classical examples of Turkish-Islamic arts of the book, we will try to observe that the conventional hilya design passed through various stages during the process of its formation. In this case the theoretical roots of Hâfiz Osman‟s hilya form and the probability of his inspiration by the aesthetic designs of the previous periods will be examined through the decorative manuscripts in religious and nonreligious topics.

Osmanlı düşünce geleneğinde Hz. Muhammed, psikolojik, fiziksel ve manevi açıdan en yüce varlık mertebesine ulaşmış yetkin insanı (el-insanü‟l-kamil) temsil etmektedir. Bu bakımdan, hat ve tezhip sanatının uygulandığı bir eser olarak hilyenin asıl amacı, Hz. Muhammed'in fiziksel görünüşünün ve ahlaki özelliklerinin estetik ifadesini ortaya koymaktır. Peygamberlik makamının yüceliğini gözler önüne seren hilyedeki mürekkep sembolizm, aynı zamanda Osmanlı toplumunun kozmolojik düşüncesini de yansıtmaktadır. Bu makalenin konusu, ünlü Osmanlı hattat Hâfiz Osman'a atfedilen klasik hilye tasarımının hat-tezhip etkileşimi ve sayı sembolizmi bağlamında incelenmesidir. Makalede Türk/İslam kitap sanatlarının klasik örneklerini incelemek suretiyle, geleneksel hilye tasarımının oluşum sürecinin çeşitli aşamalardan geçtiğini irdelemeye çalışacağız. Buna binaen, Hâfiz Osman tarafından geliştirilen hilye formunun teorik kökleri araştırılacak ve gerek dini gerekse de dini olmayan konulardaki bezemeli yazmalar üzerinden sanatkarın önceki dönemlere ait estetik tasarımlardan esinlenme olasılığı incelemeye tabi tutulacaktır.
Hilye Tasarımının Oluşumuna İlişkin Notlar: Hat-Tezhip Etkileşimi ve Sayı Sembolizmi
Keywords: Etnik Çalışmalar; Tarih; Dil ve Dil Bilim; Edebiyat; Edebi Teori ve Eleştiri